Pengaruh Latihan Zig-Zag dan Shuttle Run terhadap Hasil Kelincahan pada Karateka Dojo Ziezoyuki Academy - Kadek Yogi Parta Lesmana (Journal for Lesson and Learning Studies, 2023)
The agility of Karate athletes is still low. It is evident that when participating in the match, the athlete’s movements appear to be less agile when avoiding the opponent’s attack. The purpose of this study was to analyze zig-zag and shuttle run training in improving agility in Karateka. This study used a quasi-exsperimen method with a pre-test and post-test design control group. The population in this study were all Karateka athletes consisting of 20 male athletes and 18 female athletes. The sample used was 20 male athletes who were still actively training. Data collection methods used observation, tests and documentation. Data analysis techniques used quantitative analysis. The results showed that shuttle run training had a significant effect on increasing agility (tit equal to 60.42 more than ttab equal to 2.26). Ziq-zaq exercise gives a significant effect on increasing agility (thit equal to 159.06 more than ttab equal to 2.26). Ziq-zaq run training is more effective in increasing agility compared to shuttle run training (thit equal to 26.64 more than ttab equal to 2.26). The conclusion of this study is that training with the zig-zag run method is more effective in increasing agility in Karateka. The implication of this research is expected to increase the element of agility for athletes so that achievement can be achieve.